Developmental Dissociation of Serotonin-Induced Spike Broadening and Synaptic Facilitation in Aplysia Sensory Neurons - Stark, Laura L. (J Neurosci, 1999)
In sensory neurons (SNs) of adult Aplysia, serotonin (5-HT)-induced spike broadening has long been implicated as important for synaptic facilitation [spike duration–dependent (SDD) facilitation], particularly at nondepressed synapses. At depressed synapses, spike broadening has less impact on synaptic facilitation; under these conditions, 5-HT induces a spike duration–independent (SDI) form of facilitation (Byrne and Kandel, 1996). It has been difficult to dissociate clearly the cellular mechanisms underlying these two forms of facilitation. However, the observation that a major form of spike broadening emerges late in juvenile development (Marcus and Carew, 1998) provides a unique opportunity to examine the relationship between spike broadening and synaptic facilitation in juvenile Aplysia. We have identified three forms of synaptic plasticity in juvenile Aplysia: homosynaptic depression, SDD facilitation, and SDI facilitation. We show that homosynaptic depression is fully developed in the juvenile and that 5-HT reliably induces synaptic facilitation at depressed synapses. However, in nondepressed synapses, 5-HT–induced facilitation is not reliable. Further analysis revealed that the relationship between spike broadening and synaptic facilitation for nondepressed synapses is the inverse of that in adults. Surprisingly, in juveniles, minor spike broadening induced by 5-HT results in significant synaptic facilitation, whereas major spike broadening, when it occurs, does not. These results suggest a model in which juvenile synapses predominantly use SDI facilitation, and with the emergence of major spike broadening, a developmentally transient inhibitory process emerges. This inhibitory process seems to be independent of major spike broadening induced by 5-HT because directly broadening the spike with 4-aminopyridine induces adult-like SDD synaptic facilitation. Finally, in the adult, the inhibitory process is either lost or masked, and SDD facilitation predominates at nondepressed synapses.